Dependence of Ascorbic Acid Content in Nettle Leaf Extracts on Cryoextraction Conditions - Shcheniavskyi, Ivan; Akhatova, Yuliia (Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(1):054–058